Case reportCase report on a patient with lupus panniculitis - Bednarek, Agata; Bartoszak, Leszek; Samborski, Włodzimierz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Lupus panniculitis is a rare variant of lupus erythematosus. It may occur as a separate disease or coexist with systemic or discoid lupus erythematosus. It is characterized by persistent, tender and hard nodules localised on the face, arms, shoulders, breast and buttocks. Healing of lesions is associated with scarring, lipoatrophy and rarely ulceration. Treatment of lupus panniculitis depends on disease advancement or concomitance of additional lupus erythematosus symptoms. We report a case of a 44-year-old patient with lupus panniculitis treated with chloroquine and glucocorticosteroids, including high dose infusions. Despite intense treatment, the patient developed symptoms that suggested a diagnosis of systemic lupus erythematosus.